Corporate governance and firm performance: a longitudinal study - Haron, Razali; Abdul Manan, Abdul Syakur (2020)
This study examines the corporate governance mechanisms and how they affect firm performance in Malaysia. Using a huge data on Malaysian firms for 16 observation years (2002-2017), this study found that certain CG mechanisms do have significant impact on firm performance. Board size and board independence are positively related to firm performance. CEO duality is negatively related to firm performance, in support of the separation of roles between Chairman and CEO of firm. Agency theory seems to be the dominant theory influencing the corporate governance structure of firms in Malaysia.